Environmental Characteristics of the Mining Area of Ni–Cu–Fe Paleoproterozoic PGE Monchepluton Intrusion (NE Scandinavia) - Miłosz Huber; Stanisław Chmiel; Olga Iakovleva (Mining, 2022)
The problem of dump recultivation associated with sulfide ore mining is always a challenge for ecologists. A special case is the Arctic, where the specific climate and short vegetative period mean that any traces of such activities can persist for many years. The Monchepluton massif is a Paleoproterozoic, layered Platinum Group Element (PGE) intrusion, which is located in NE Scandinavia, beyond the Arctic Circle. This intrusion is mainly composed of ultramafic and alkaline rocks, represented by dunites, harzburgites, orthopyroxenites, norites, and gabbronorites. In these rocks, there is mineralization of the oxide ores Cr, Fe, and Ti, as well as the sulfide ores Cu, Ni, Fe, and PGE. The massifs of this intrusion were mined in the 20th century. The traces of intensive mining in the area are still visible today. The purpose of this study was to demonstrate the state of the environment and propose its rehabilitation. The authors carried out an inventory of the mining facilities and studies of the area’s rocks, soils, plants, and waters. The results of these studies unequivocally show that the current condition of the site indicates the conditions for an ecological disaster. The most important polluting factor is the presence of metallurgical plants, which are responsible for acid rain and soil pollution. Another threat is uncontrolled mine water outflows. Due to the specific climatic conditions and the vegetation found in the area, the process of rehabilitating the area may be costly and lengthy.